A comparison of plasma and gaseous nitriding for tools in hot massive forming. (September 2013) - Hoja, S.; Klümper-Westkamp, H.; Hoffmann, F.; Zoch, H-W.
Abstract : Tools for hot massive forming are exposed to complex loads. The abrasive wear of the thermally, mechanically and tribologically most loaded part of the engraving is the main cause of failure. In order to resist the high loads, the surfaces and boundary areas of the tools are nitrided. As an alternative to gaseous nitriding the tools are also treated by salt bath nitrocarburising. Plasma nitriding is only rarely used. But the plasma treatment has some advantages over gaseous nitriding. For example partial treatments can be carried out more easily and cleaner. Steels with higher alloy content can be easily nitrided because the protecting oxide layer on the surface, which sometimes occurs, can be removed by a sputtering step before nitriding. The investigations concern the nitriding treatment of the steels 1·2367 and 1·2344, which are often used in hot massive forming. The nitriding experiments could be carried out in a gas nitriding furnace and two different plasma nitriding furnaces, therefore a comparison of the nitriding media gas and plasma was possible as well as a comparison of the treatment in different plasma nitriding furnaces. One of the furnaces was also provided with an active screen, therefore it was possible to do active screen plasma nitriding (ASPN) in addition to conventional plasma nitriding. The advantages and disadvantages of the different treatment technologies are discussed in respect of their suitability for forging tools.